A Comparative Evaluation of the Radiopacity of Contemporary Restorative CAD/CAM Blocks Using Digital Radiography Based on the Impact of Material Composition - Elhelbawy, Nahla Gamal; Ghouraba, Rehab F; Hasaneen, Fatma A (International Journal of Biomaterials, 2022)
Purpose. The main purpose of this study was to assess the radiopacity of contemporary restorative computer-aided design (CAD)/computer-aided manufacturing (CAM) materials and the impact of material composition as measured by energy-dispersive X-ray spectrophotometry (EDX) on radiopacity. Materials and Methods. Ten specimens of six CAD/CAM materials with 1 mm thickness were produced and then digitally radiographed with an aluminum (Al) step-wedge (SW) and 1 mm thick tooth slice. The specimen mean gray values (MGVs) were recorded in pixels and compared to an Al-SW, dentin, and enamel of equal thickness. For the elementary analysis of the composition of the materials, EDX was performed. Results. The recorded MGVs ranged between 21.20 ± 4.94 and 238.5 ± 13.61 pixels. Materials were sorted according to the MGVs descendingly, Prettau, Vita Suprinity, Vita Enamic, Shofu, Pekkton, and BioHPP. Prettau and Vita Suprinity had significantly higher MGV than dentin and 1 mm thick Al. In comparison, Vita Enamic had a slightly higher value than dentin and 1 mm thick Al. Although Pekkton and BioHPP had MGV significantly lower than dentin and 1 mm thick Al, Shofu had a significantly lower value than dentin and nonsignificantly lower than 1 mm thick Al (p < 0.05). According to EDX analysis, the examined materials contained several components in varying quantities of radiopacity. Conclusions. The radiopacity of only three studied materials exceeded the International Organization for Standardization’s minimum standards (ISO).